Fiber cloth, prepreg, metal foil-clad plate and manufacturing method of fiber cloth
By adjusting the structural parameters of the fiber cloth and using ultrasonic dipping and strong thermal desizing technology, the problem of filament and hairiness during the processing process is solved, and a fiber cloth with high strength, high density and low CTE is achieved, thereby improving the performance of the metal foil plate.
Patent Information
- Application Number
- CN202311220591.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
AI Technical Summary
The existing fiber cloth has problems such as broken wire and hair during processing, resulting in low production efficiency and high thermal expansion coefficient of the product, making it difficult to meet the needs of low CTE and low loss.
By adjusting the single filament diameter, braid density and number of single filament roots of the fiber cloth, combined with ultrasonic dipping and strong thermal desizing technology, the strength and density of the fiber cloth will be improved, the wire breaking problem during the braiding process will be improved, and the content of the resin matrix will be reduced to reduce the thermal expansion coefficient.
The high strength and high density of the fiber cloth are achieved, the production efficiency is improved, the thermal expansion coefficient and loss are reduced, and the dimensional stability and heat resistance of the metal-covered foil plate are improved.
Smart Images

Figure CN119663509A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of printed circuit boards, and specifically, to a fiber cloth, a prepreg, a metal-clad laminate, and a method for manufacturing the fiber cloth. Background Art
[0002] The main components of a printed circuit board (PCB) include a copper-clad laminate and a prepreg, and the main components of the copper-clad laminate and the prepreg include a reinforcing material, a resin material, a copper foil, and a filler. To support the simultaneous realization of a low coefficient of thermal expansion (CTE) and low transmission loss technology of the PCB, in the prior art, a glass fiber cloth with both a relatively low CTE and a low Dk / Df is usually used as the reinforcing material. As the CTE and Df of the copper-clad laminate / prepreg are further reduced, the industry is exploring the use of a quartz fiber cloth with both low CTE and low loss characteristics as the reinforcing material.
[0003] However, the special glass formula of the above type of fiber cloth developed to achieve low loss characteristics has low fiber strength and high brittleness. During fiber forming and drawing and fiber cloth manufacturing, problems such as broken filaments and hairiness are likely to occur, resulting in difficulties in processing the fiber cloth and low production efficiency. Summary of the Invention
[0004] The present application provides a fiber cloth, a prepreg, a metal-clad laminate, and a method for manufacturing the fiber cloth, which can make the fiber cloth have both high strength and high density and improve the production efficiency of the fiber cloth.
[0005] In a first aspect, a fiber cloth is provided, which includes a plurality of bundles of warp yarns and a plurality of bundles of weft yarns. The warp yarns and the weft yarns are respectively formed by twisting a plurality of single filaments. The weaving density of the warp yarns is X threads per inch, the weaving density of the weft yarns is Y threads per inch, the number of single filaments in each bundle of warp yarns is x, the number of single filaments in each bundle of weft yarns is y, the diameter of each single filament in each bundle of warp yarns is Dx μm, the diameter of each single filament in each bundle of weft yarns is Dy μm, and the thickness of the fiber cloth is t μm. The fiber cloth satisfies any one of the following two conditions: t ≤ 20 μm, 4 μm < Dx ≤ 6 μm, 4 μm < Dy ≤ 6 μm, X + Y ≥ 180 threads per inch, x + y ≤ 150, or 20 μm < t ≤ 60 μm, 5 μm < Dx ≤ 10 μm, 5 < Dy ≤ 10 μm, X + Y ≥ 100 threads per inch, x + y ≤ 300.
[0006] In the embodiments provided by the present application, for fiber cloths with different thickness ranges, by increasing the filament diameters of the warp and weft yarns in the fiber cloth, adjusting the knitting density of the warp and weft yarns, and the number of filaments in the bundle, the fiber cloth can have high strength and high density, thereby being able to improve the problem of broken filaments generated during the knitting process of the fiber cloth, improve the production efficiency of the fiber cloth, and can also improve the problem of high coefficient of thermal expansion of the prepreg and metal-clad laminate products caused by the low knitting density of the thin fiber cloth. In addition, the increase in the diameters of the warp and weft yarns in the fiber cloth can reduce the specific surface area of the fiber filaments, improve the interfacial loss of the fiber cloth, and thus contribute to improving the loss of the metal-clad laminate; moreover, the increase in diameter can make the bending degree of the weft yarn smaller and the flatness of the fiber cloth better, which is beneficial to improving the dimensional stability of the metal-clad laminate and reducing problems such as the exposure of the weave pattern. The reduction in the number of filaments in the warp and weft yarns can reduce the difficulty of the fiber opening process, and can effectively improve the wetting effect of the fiber cloth during the coupling agent treatment and resin sizing process, which is beneficial to the adsorption of the coupling agent and the penetration of the resin, thereby enhancing the interfacial bonding force between the glass fiber cloth and the resin and further improving the heat resistance of the metal-clad laminate.
[0007] Combined with the first aspect, in some implementation manners of the first aspect, the basis weight of the fiber cloth is W g / m 2 , and the fiber cloth further satisfies the following conditions: when t ≤ 20 μm, 1.3 < t / (Dx + Dy) ≤ 2, W / t ≥ 0.85×10 6 g / m 3 .
[0008] Combined with the first aspect, in some implementation manners of the first aspect, the basis weight of the fiber cloth is W g / m 2 , and the fiber cloth further satisfies the following conditions: when 20 μm < t ≤ 60 μm, 2 < t / (Dx + Dy) ≤ 5, W / t ≥ 0.85×10 6 g / m 3 .
[0009] In the embodiments provided by the present application, when t ≤ 20 μm, the fiber cloth further satisfies 1.3 < t / (Dx + Dy) ≤ 2 and W / t ≥ 0.85×10 6 g / m 3 , or when 20 μm < t ≤ 60 μm, the fiber cloth further satisfies 2 < t / (Dx + Dy) ≤ 5, W / t ≥ 0.85×10 6 g / m 3 , which can make the fiber cloth have high density, improve the problem of broken filaments generated during the knitting process of the fiber cloth, and can ensure that the Tex value and basis weight of the fiber cloth are similar to those in the prior art, expanding the application range of the fiber cloth.
[0010] In combination with the first aspect, in certain implementations of the first aspect, when t ≤ 20 μm, 5 μm ≤ Dx = Dy ≤ 6 μm.
[0011] In combination with the first aspect, in certain implementations of the first aspect, when 20 μm < t ≤ 60 μm, 7 μm ≤ Dx = Dy ≤ 10 μm.
[0012] In combination with the first aspect, in certain implementations of the first aspect, X = Y.
[0013] In combination with the first aspect, in certain implementations of the first aspect, x = y.
[0014] In combination with the first aspect, in certain implementations of the first aspect, the fiber cloth is any one of E - glass fiber cloth, low Dk / Df glass fiber cloth, and quartz fiber cloth.
[0015] In a second aspect, a prepreg is provided, including the fiber cloth as described in the first aspect or any possible implementation of the first aspect and a resin matrix, the resin matrix is disposed on the surface of the fiber cloth, and the thickness of the resin matrix is 3 μm to 15 μm.
[0016] In combination with the second aspect, in certain implementations of the second aspect, the thickness of the resin matrix is 4 μm to 6 μm.
[0017] In the embodiments provided in the present application, by reducing the thickness of the resin matrix on the fiber surface, the content of the resin matrix in the prepreg can be reduced, thereby reducing the coefficient of thermal expansion of the metal - clad laminate. By selecting a high - density fiber cloth with a suitable structure, basis weight, and thickness, the impregnation effect of the fiber cloth is better, and problems such as delamination and lack of glue caused by low resin content are not likely to occur.
[0018] In combination with the second aspect, in certain implementations of the second aspect, the difference between the thickness of the fiber cloth and the thickness of the prepreg is 6 μm to 30 μm.
[0019] In combination with the second aspect, in certain implementations of the second aspect, the difference between the thickness of the fiber cloth and the thickness of the prepreg is 8 μm to 12 μm.
[0020] In the embodiments provided in the present application, by controlling the thickness difference between the fiber cloth and the prepreg, the content of the resin matrix in the prepreg can be reduced, thereby enabling the acquisition of a metal - clad laminate with a coefficient of thermal expansion.
[0021] In a third aspect, a metal - clad laminate is provided, including the prepreg as described in the second aspect or any possible implementation of the second aspect and at least two metal foils, the prepreg is disposed between the at least two metal foils.
[0022] In a fourth aspect, a method for manufacturing a fiber cloth is provided, which is used to manufacture the fiber cloth as described in the first aspect or any possible implementation method of the first aspect, comprising: coating a wetting agent on the surface of the fiber filaments, the main component of the wetting agent being an organic matter with an initial thermal decomposition temperature lower than 350°C and being water-soluble; sizing the fiber yarn during the warping process, the main component of the slurry being an organic matter with an initial thermal decomposition temperature lower than 350°C and being water-soluble, the fiber yarn being formed by twisting a plurality of the fiber filaments; weaving the sizing fiber yarn into a fiber cloth; and ultrasonically cleaning the fiber cloth in a temperature range of 60°C to 95°C.
[0023] In the embodiments provided in the present application, organic matter with an initial thermal decomposition temperature lower than 350°C and being water-soluble is used as the main component of the sizing agent and the sizing, which can reduce the difficulty of desizing, so that the sizing agent and the sizing agent are easily removed in the subsequent desizing process without the need for ultra-high temperature strong thermal desizing treatment for desizing; the fiber cloth is ultrasonically washed in the temperature range of 60°C to 95°C to replace the traditional strong thermal desizing method to remove the sizing agent and the sizing agent, which can avoid damage to the strength of the fiber cloth caused by strong thermal desizing, improve the tensile strength of the fiber cloth and improve the surface quality of the fiber cloth, so that the fiber cloth is not prone to problems such as broken wires and hairiness during processing and subsequent use.
[0024] In combination with the fourth aspect, in certain implementations of the fourth aspect, the solution used in the ultrasonic immersion process is any one of the following solutions: pure water, methanol solution, ethanol solution, and ether organic solution.
[0025] In the embodiments provided in the present application, the ultrasonic immersion process uses methanol solution, ethanol solution or ether organic solution as a solvent, which can accelerate the dissolution of the slurry and the wetting agent and facilitate the removal of the slurry and the wetting agent. Using pure water as a solvent is more environmentally friendly and has lower cost.
[0026] In combination with the fourth aspect, in certain implementations of the fourth aspect, before ultrasonically cleaning the fiber cloth, the method further includes: swelling the fiber cloth with any one of an oxidant aqueous solution, a weak alkali aqueous solution and an ether organic solution.
[0027] In the embodiments provided in the present application, an aqueous oxidant solution is used as a solvent to perform swelling treatment on the fiber cloth, so that the slurry and wetting agent on the surface of the fiber cloth can be oxidized and hydrolyzed, and a weak alkaline aqueous solution or an ether organic solution can accelerate the dissolution of the slurry and the wetting agent, so that the slurry and the wetting agent can be partially removed or swelled, thereby making the slurry and the wetting agent easier to remove in the subsequent ultrasonic cleaning process.
[0028] In combination with the fourth aspect, in certain implementations of the fourth aspect, the solution temperature used in the swelling treatment is 60° C. to 95° C., and the concentration is 0.1% to 5%.
[0029] In the embodiments provided in the present application, the solution used in the swelling treatment process, that is, the oxidant aqueous solution, the weak alkali aqueous solution or the ether organic solution has a temperature of 60°C to 95°C and a concentration of 0.1% to 5%, which can improve the swelling effect of the slurry and the wetting agent, making the slurry and the wetting agent easier to remove.
[0030] In combination with the fourth aspect, in certain implementations of the fourth aspect, the processing time of the ultrasonic immersion is greater than or equal to 10 s.
[0031] In the embodiments provided in the present application, the ultrasonic immersion process with a treatment time greater than or equal to 10 seconds can improve the removal effect of the slurry and the wetting agent.
[0032] In combination with the fourth aspect, in certain implementations of the fourth aspect, after the fiber cloth is ultrasonically cleaned, the method further includes: performing a strong heat desizing treatment on the fiber cloth obtained by the ultrasonic cleaning process, and the treatment temperature of the strong heat desizing process is 320°C to 380°C, and the time is 20h to 40h.
[0033] In the embodiments provided in the present application, strong heat desizing is performed after the ultrasonic immersion treatment, and the treatment temperature of the strong heat desizing process is 320°C to 380°C, and the time is 20h to 40h, which can further improve the removal effect of the slurry and the wetting agent and reduce the amount of organic residue on the surface of the fiber cloth. In addition, the treatment temperature of the strong heat desizing process is 320°C to 380°C, which can reduce the negative damage of strong heat to the strength of the fiber cloth and improve the surface quality of the fiber cloth.
[0034] In combination with the fourth aspect, in certain implementations of the fourth aspect, the metal roller used in the intense thermal desizing process is an alloy metal having a thermal expansion coefficient less than or equal to 10 ppm / °C.
[0035] In the embodiments provided in the present application, the thermal expansion coefficient of the metal roller used in the strong thermal desizing process is less than or equal to 10 ppm / °C, which can reduce the stress on the fiber cloth caused by the thermal expansion of the metal roller.
[0036] In combination with the fourth aspect, in certain implementations of the fourth aspect, after the fiber cloth obtained by the ultrasonic immersion process is subjected to a strong thermal desizing treatment, the method further includes: treating the fiber cloth with a coupling agent, and alkylating the coupling agent-treated cloth with a small molecule silane.
[0037] In the embodiments provided in the present application, the fiber cloth is alkylated with small molecule silane, which can effectively remove some of the excess hydroxyl groups on the surface of the fiber cloth, improve the loss of the fiber cloth, and further achieve low loss of the metal foil-clad plate.
[0038] In combination with the fourth aspect, in certain implementations of the fourth aspect, the coupling agent treatment is performed at least twice, and the steric hindrance effect of the coupling agent used in each coupling agent treatment after the first coupling agent treatment is less than the steric hindrance effect of the coupling agent used in the first coupling agent treatment.
[0039] In the embodiments provided in the present application, the number of coupling agent treatments is at least two times, and the steric hindrance effect of the coupling agent used in the subsequent coupling agent treatment is smaller than the steric hindrance effect of the coupling agent used in the first coupling agent treatment, which can improve the reaction activity of the subsequent coupling agent treatment process, and the coupling agents used in the two coupling agent treatments can synergize to improve the reliability of the interface.
[0040] In combination with the fourth aspect, in certain implementations of the fourth aspect, the coupling agent is a silane coupling agent, and the silane coupling agent is one or more of the following: γ-aminopropyltriethoxysilane, vinyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, tris(trimethoxysilylpropyl)isocyanurate, 3-(2,3-epoxypropoxy)propyltriethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane, dodecyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane.
[0041] In combination with the fourth aspect, in certain implementations of the fourth aspect, the small molecule silane is any one of the following silanes: methyltrimethoxysilane, methyltriethoxysilane, and trimethylchlorosilane. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The application architecture of the metal foil-clad plate provided in the embodiment of the present application.
[0043] Figure 2 This is a schematic diagram of the overall structure of the fiber cloth provided in an embodiment of the present application.
[0044] Figure 3 This is a schematic side view of the fiber cloth provided in an embodiment of the present application.
[0045] Figure 4 A method for manufacturing the fiber cloth provided in an embodiment of the present application.
[0046] Figure 5This is a comparison chart of the changes in surface organic matter content of the fiber cloth provided in the embodiment of the present application and the fiber cloth in the prior art under thermogravimetric analysis conditions.
[0047] Figure 6 This is a schematic diagram of the structure of the prepreg provided in an embodiment of the present application. DETAILED DESCRIPTION
[0048] The technical solution in this application will be described below in conjunction with the accompanying drawings.
[0049] References to "one embodiment" or "some embodiments" etc. described in this specification mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. appearing in different places in this specification do not necessarily all refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways.
[0050] The terms "include", "comprising", "having" and variations thereof all mean "including but not limited to", unless specifically emphasized otherwise.
[0051] In the embodiments of the present application, the number of nouns, unless otherwise specified, means "singular noun or plural noun", that is, "one or more". "At least one" means one or more, "more" means two or more, and "many" in "one or more" also means two or more.
[0052] The electrical connection between the substrate and the printed circuit board (PCB) or electronic components in the board-level architecture is achieved through soldering with solder balls or solder paste. During the assembly and soldering process, the substrate and the printed circuit board or electronic components will be heated and their sizes will change due to the need to heat the solder balls / solder paste. When the coefficient of thermal expansion (CTE) of the substrate, PCB, and components in the plane direction differs greatly or the soldering size becomes larger, there will be internal stress at the solder joint position due to inconsistent deformation during the heating and cooling process during assembly. The greater the CTE difference or the larger the component size, the greater the stress. When the stress exceeds the welding connection force, problems such as solder joint cracking will occur, resulting in electrical connection failure. In addition, when electronic products are in service in the market, the solder joints between the PCB and the components will also be subjected to long-term thermal fatigue stress, or creep fatigue, due to the difference in CTE between the components and the PCB, as well as the temperature difference between the device and the PCB, and eventually the solder joints will crack and fail.
[0053] Figure 1 This is a schematic diagram of the PCB application architecture, such as Figure 1 As shown in (a), the wafer 103 is soldered to the substrate 105 through the solder ball 106, and is packaged with plastic ceramics, that is, the package shell 104 shown in the figure is formed, together forming a ball grid array (BGA) component 103. Further, the BGA component is fixedly connected to the PCB 101 through the solder ball 102. The wafer 103 can be a silicon wafer, and its plane expansion coefficient (in the xy direction shown in the figure) is relatively small, about 2 to 10ppm / ℃, the plane expansion coefficient of the package substrate 105 is usually greater than the plane expansion coefficient of the wafer 103, the plane expansion coefficient is ≤12ppm / ℃, and the plane expansion coefficient of the PCB 101 is usually 15 to 20ppm / ℃. When the ambient temperature difference changes greatly in the application scenario or the equipment is repeatedly started, the stress at the solder joint is relatively large, which will affect the working life of the solder joint and also cause failure problems such as solder joint cracking.
[0054] The application architecture of PCB is gradually tending to directly solder components on the PCB board, such as Figure 1 As shown in (b), the transitional packaging substrate 105 between the PCB 101 and the component 103 is eliminated, and the wafer 102 is directly soldered to the PCB 101 through the solder balls 102, which further increases the CTE difference between the PCB and the component.
[0055] Substrates and circuit board materials are usually composed of polymer resins, fillers, fiber cloth, etc., and their CTE is generally larger than that of inorganic materials such as ceramics and silicon. Therefore, in order to improve the reliability problems caused by CTE mismatch, it is usually hoped that the CTE of substrate materials and PCB dielectric materials can be reduced to match components.
[0056] At the same time, as electronic products tend to have high information transmission rates and large information transmission capacities, substrates and PCBs tend to develop towards high speed and high density. Accordingly, the transmission loss of substrate materials and PCB dielectric materials is required to be lower and lower, which requires materials with lower loss (dissipation factor, Df). In addition, the routing and vias are becoming more and more dense, and the size of components (such as chips) is getting larger and larger, resulting in an increasing risk of connection failure such as solder joint cracking, which also requires reducing the CTE characteristics of substrate and PCB dielectric materials.
[0057] Therefore, for the dielectric materials of substrates and PCBs, how to simultaneously have low CTE and low loss performance to meet product reliability and high-speed signal transmission requirements is a technical challenge faced by substrate materials and PCB materials, especially when ultra-low CTE (such as CTE≤10ppm / ℃) and ultra-low Df (such as Df≤0.001@10GHz, that is, the loss factor at a frequency of 10GHz is ≤0.001), the challenge is extremely great.
[0058] In order to solve the problem of CTE mismatch between components and substrates and PCBs in the XY direction, the cracking and failure of solder joints caused by the increase in component size or repeated temperature changes, and the low-loss performance of substrates / PCBs, the existing technologies use the following solutions:
[0059] Develop dielectric materials with both low CTE and low loss properties, such as prepreg (PP) and copper clad laminate (CCL). Use these materials to make PCBs to reduce the CTE mismatch between components and PCBs, thereby reducing stress at solder joints. At the same time, the low loss property can ensure the signal transmission performance of substrates and PCBs.
[0060] Generally speaking, the CTE of copper clad laminate is mainly affected by polymer resin, filler, reinforcement material and copper foil. According to the Turner model, the relationship is as follows:
[0061]
[0062] Where: α-thermal expansion coefficient; K-bulk modulus; -volume percentage; r-resin; f-filler; g-reinforcement material; c-copper foil.
[0063] Since the electronic copper foil used in copper clad laminates is mostly electrolytic copper or rolled copper with a purity of more than 99.5%, its CTE is generally around 17ppm / ℃. The main factor affecting the CTE of copper clad laminates is polymer resin, followed by reinforcing materials (glass fiber cloth, etc.) and filling materials (fillers, etc.). Among them, for the CTE in the plane direction of the dielectric material (xy direction shown in the figure), the CTE of the reinforcing material is the key influencing factor.
[0064] Similarly, the main factors affecting the dielectric loss factor (Df) performance of copper clad laminates are polymer resins, reinforcing materials and filling materials.
[0065] D fccl =V A Df A +V B Df B +V C Df C
[0066] Where: V-volume percentage; Df-loss factor; A-resin, B-filler, C-glass fiber cloth.
[0067] In order to obtain copper clad laminates with low CTE and low dissipation factor (Df), the existing technologies use the following solutions: (1) In terms of reinforcing materials, reinforcing materials with both low CTE and low Df are used, such as quartz fiber cloth, low dielectric constant (Dk) or low Df glass fiber cloth. In particular, when the copper clad laminate material is required to have ultra-low CTE (such as CTE≤10ppm / ℃) and ultra-low Df (such as Df≤0.001@10GHz), quartz fiber cloth and low Dk / Df glass fiber cloth are one of the key materials that must be used. (2) In terms of resin, resins with both low CTE and low Df are used. However, when ultra-low CTE and ultra-low Df are required, such as CTE≤40ppm / ℃ and Df≤0.001@10GHz, there are very few types of resins that meet the requirements, and the price is also very high. (3) In terms of fillers, the filling ratio of fillers can be increased to achieve low CTE and low Df, such as a filling ratio > 60% wt. However, the increase in fillers may lead to problems such as difficulty in subsequent drilling processing. In order to balance issues such as brittleness, processability, and reliability, the filler can only be filled to a certain ratio.
[0068] In summary, the use of quartz fiber cloth, low Dk / Df glass fiber cloth, etc. in low CTE and low loss copper clad laminate dielectric materials is one of the common measures to reduce CTE and Df, especially quartz fiber cloth, which has both ultra-low CTE and ultra-low Df properties and is one of the potential ideal materials for low CTE and low loss panels.
[0069] However, for reinforcing materials that can improve both CTE and Df performance, such as low Dk / Df glass fiber cloth and quartz fiber cloth, the following problems still exist in current applications.
[0070] First, low Dk / Df glass fiber and quartz fiber have high melting temperature, high melt viscosity and difficult molding operation. Ultrafine fiber (≤10μm) is more likely to have problems such as broken ends and flying wires during molding and processing than electric glass fiber cloth (E-glass, or E-glass fiber cloth), which affects the appearance quality of the cloth. At the same time, the tensile modulus of low-loss glass fibers such as the first-generation low Dk / Df and the second-generation low Dk / Df is much smaller than that of E-glass, and it is more likely to have broken wires during processing. Although the theoretical modulus of quartz glass is very high, about 75 to 80GPa, the actual measured fiber strength is much lower than this value. The main factors affecting strength are firstly the surface defects of glass, especially the size and depth of surface microcracks, which have the most obvious influence; secondly, internal defects, such as impurities, uneven melting and residual stress, etc., and quartz glass fiber is brittle, and it is more likely to have broken wires and other problems during the processing and manufacturing of fiber cloth and copper-clad laminate processing, resulting in the appearance of rubber particles and bumps after impregnation into PP. In addition, since the fiber cloth manufacturing process requires the application of sizing agents, sizing agents, etc. on the fiber surface to bundle and protect the fiber from broken fibers, hairiness, and other problems during the weaving process, the sizing agent needs to be removed after the weaving is completed, and this removal generally uses a heat treatment process. Generally speaking, the strength of the glass fiber will decrease to a certain extent after the heat treatment process is used for desizing. During the subsequent coupling agent treatment or PP gluing, it is more likely to cause fiber cloth breakage or fiber filament / fiber yarn breakage, resulting in fluffing, and other problems than E-glass. Especially when the monofilament diameter is small (≤6μm), there are many broken fibers and it is difficult to form. 5.0μm, 4.5μm and 4.0μm monofilaments are the standard specifications for ultra-thin fiber cloths below 50μm in the IPC standard, which makes the processing of ultra-thin cloth difficult, inefficient, and costly.
[0071] Secondly, although the bulk loss factor of low Dk / Df glass is Df≤0.003@10GHz and the bulk loss factor of quartz glass is Df≤0.0002@10GHz, during the fiber forming and weaving processes, due to incomplete desizing of some fiber surfaces, the generation of hydroxyl groups on the surface during fiber forming and processing, and increased losses due to interface treatment, the Df performance of low Dk / Df glass cloth and quartz fiber cloth in copper clad laminates is much greater than the loss of the glass itself.
[0072] Therefore, the present application provides a fiber cloth, a prepreg, a metal foil-clad plate, and a method for manufacturing the fiber cloth to achieve high strength and high density performance of the fiber cloth, improve the problem of broken wires during fiber cloth processing, and improve production efficiency to support the realization of low CTE and low loss performance of PCB.
[0073] Figure 2 This is a schematic diagram of the overall structure of a fiber cloth provided in an embodiment of the present application. Figure 3 for Figure 2 Side view of the fiber cloth shown. The fiber cloth can be any one of E-glass fiber cloth, low Dk / Df glass fiber cloth, and quartz fiber cloth. The fiber cloth can be woven from fiber yarns, and the weaving method can be plain weave, twill weave, satin weave, etc. Figure 2 Schematically shows a fiber cloth woven by a plain weave method. As Figure 2 shown, the fiber cloth 100 can be woven from warp yarns 101 and weft yarns 102. The warp yarns 101 and the weft yarns 102 are arranged at intervals, one above the other. The warp yarns 101 and the weft yarns 102 are交错 once every bundle of yarns. That is, with the warp yarn 101 as a reference, when the current weft yarn 102 is located above the warp yarn 101, the next bundle of weft yarns 102 is located below the warp yarn 101. Similarly, with the weft yarn 102 as a reference, when the current warp yarn 101 is located above the weft yarn 102, the next bundle of warp yarns 101 is located below the weft yarn 102, and they are arranged交错 in sequence to form a plain weave structure.
[0074] Each bundle of warp yarns 101 and weft yarns 102 can also be respectively referred to as warp-direction fiber yarns and weft-direction fiber yarns, or collectively as yarn bundles. Each bundle of yarns can be twisted from multiple filaments or multiple fiber filaments at a certain twist. That is, multiple filaments can be twisted along the axial direction so that the multiple filaments are抱合 into a yarn bundle. As Figure 3 shown, each bundle of warp yarns 101 can be twisted from multiple filaments and is arranged at intervals above and below the weft yarns 102. Similarly, each bundle of weft yarns 102 can also be twisted from multiple filaments to improve the strength, wear resistance, and other properties of the fiber cloth. Exemplarily, the twist of the warp yarns 101 and the weft yarns 102 can be 0.5Z r / inch (revolutions per inch, the number of turns of the single filament per inch), 0.7Z r / inch, or 0.9Z r / inch, etc. Z can represent counterclockwise twisting.
[0075] In some embodiments, assuming the weaving density of the warp yarns is X roots per inch, the weaving density of the weft yarns is Y roots per inch, the number of single filaments in each bundle of warp yarns is x, the number of single filaments in each bundle of weft yarns is y, the diameter of each bundle of warp yarns is Dx μm, the diameter of each bundle of weft yarns is Dy μm, and the thickness of the fiber cloth is t μm, and the basis weight of the fiber cloth is set as W g / m 2 , the fiber cloth can satisfy: when t ≤ 20, 4 < Dx ≤ 6 μm, 4 < Dy ≤ 6 μm, X + Y ≥ 180 roots per inch, x + y ≤ 150 roots, or can satisfy: when 20 μm < t ≤ 60 μm, 5 μm < Dx ≤ 10 μm, 5 < Dy ≤ 10 μm, X + Y ≥ 100 roots per inch, x + y ≤ 300 roots.
[0076] Table 1
[0077]
[0078] Table 1 shows examples of the monofilament diameter and number of filaments of the fiber cloth provided in the embodiments of the present application. On the premise of ensuring that the Tex value of the fiber cloth is kept at the same level as the existing technical specifications, the strength of the fiber cloth can be improved by producing monofilaments with a larger diameter and reducing the number of monofilaments in the fiber bundle. The reduction in the number of monofilaments can be adjusted based on the increase in the monofilament diameter. The Tex is a unit of linear density, which refers to the number of grams of the weight of a 1000-meter-long yarn at the standard regain. The larger the gram weight, the thicker the yarn. When weaving, the warp and weft densities of the fiber bundle can be adjusted to obtain a fiber cloth with the same basis weight as the existing IPC standard. Among them, the fiber cloth 1 corresponding to numbers 1 to 6 can be a fiber cloth with a thickness t ≤ 20 μm, the fiber cloth 1 corresponding to numbers 7 to 10 can be a fiber cloth with a thickness of 20 μm < t ≤ 60 μm, the fiber cloth 2 corresponding to numbers 1 to 3 can be a fiber cloth with a thickness t ≤ 20 μm, and the fiber cloth 2 corresponding to numbers 4 to 10 can be a fiber cloth with a thickness of 20 μm < t ≤ 60 μm.
[0079] Table 2
[0080]
[0081] Table 2 shows a comparison example of the diameter and number of monofilaments of another fiber cloth provided in the embodiments of the present application. Compared with the existing yarn types, the fiber cloth provided in the embodiments of the present application has a larger monofilament diameter and a smaller number of monofilaments. The monofilament diameter increases by 0.5 μm to 4 μm compared with the existing yarn types, and the number of monofilaments decreases by 1 / 5 to 1 / 2. In this example, when weaving, the warp density and weft density can be slightly reduced so that the Tex value of the fiber cloth is slightly greater than that of the existing yarn types, thereby ensuring that the resin content of the prepreg and the fiber cloth specifications matched with a prepreg of a certain thickness are consistent with the existing usage habits, and making the basis weight of the fiber cloth consistent with or close to the existing specifications, so as to facilitate the design and application of the fiber cloth and expand the application range of the fiber cloth.
[0082] Further, the fiber cloth can also meet the following conditions: when t ≤ 20 μm, 1.3 < t / (Dx + Dy) ≤ 2, W / t ≥ 0.85 × 10 6 g / m 3 , or it can meet: when 20 μm < t ≤ 60 μm, 2 < t / (Dx + Dy) ≤ 5, W / t ≥ 0.85 × 10 6 g / m 3 .
[0083] When the fiber cloth meets the above conditions, it can further ensure the high-density and high-strength performance of the fiber cloth, and enable the fiber cloth to have a Tex value or basis weight similar to that of the fiber cloth in the existing technology, so as to facilitate the design and application of the fiber cloth and expand its application range.
[0084] Table 3 is an example of another fiber cloth provided in an embodiment of the present application. By adjusting the weaving density of fiber cloths of different thicknesses and controlling the range of t / (Dx+Dy) and W / t of the fiber cloth, a fiber cloth with high strength and high density is obtained, the problem of broken wires during the weaving process of the fiber cloth is improved, and the low CTE characteristics of the copper clad laminate are achieved.
[0085] Table 3
[0086]
[0087] Table 4 is a comparison of the warp and weft strengths of the fiber cloth provided in the embodiment of the present application with the strengths of the existing fiber cloth, wherein the warp and weft strength 1 is the warp and weft strengths corresponding to the fiber cloth in the prior art, and the warp and weft strength 2 is the warp and weft strengths of the fiber cloth under the thickness, monofilament diameter, weaving density and number of monofilaments provided in the embodiment of the present application. By controlling the monofilament diameter, weaving density and number of monofilaments of the fiber cloth, the fiber cloth provided in the embodiment of the present application can have a similar basis weight to the fiber cloth in the prior art. It can be seen from Table 4 that, compared with the existing fiber cloth, the embodiment of the present application greatly improves the warp and weft strengths of the fiber cloth by increasing the monofilament diameter and adjusting the weaving density and number of monofilaments.
[0088] Table 4
[0089]
[0090]
[0091] The above is an introduction to the structure of fiber cloth. Figure 4 A method for manufacturing the fiber cloth provided in an embodiment of the present application is introduced, and the method can be used to manufacture the above-mentioned fiber cloth.
[0092] S401, coating a wetting agent on the surface of the fiber filaments, wherein the main component of the wetting agent is a water-soluble organic matter with an initial thermal decomposition temperature lower than 350°C.
[0093] The sizing agent can be applied to the fiber surface after drawing to improve the stiffness and coating of the fiber, which is beneficial to the subsequent warping, sizing and weaving processes. The main components of the sizing agent need to consider the functional requirements such as stiffness, coating, and wear resistance, as well as the feasibility of decomposition processing, that is, the process feasibility of removing the sizing agent.
[0094] The main component of the sizing agent may be a water-soluble organic matter with an initial thermal decomposition temperature lower than 350°C, and thus the sizing agent and slurry are easier to remove at a lower temperature to reduce energy consumption. For example, the initial thermal decomposition temperature of the main component of the sizing agent may be 350°C, 340°C, 330°C, 320°C, 310°C, 300°C, etc., or even lower than 300°C.
[0095] In some embodiments, after the main components of the wetting agent are treated by thermal gravimetric analysis (TGA), for example, when the temperature is increased to 10°C / min for decomposition, the residual organic matter is ≤50% when the temperature is increased to 380°C, and the residual organic matter is ≤10% after decomposition at 380°C for 2 hours, and the residual organic matter is ≤5% after decomposition for 5 hours.
[0096] The solubility of the component in an aqueous solution at 80° C. may be 100%, that is, the wetting agent may have good water solubility, so that the wetting agent can be easily removed in the subsequent ultrasonic immersion cleaning step.
[0097] Exemplarily, the main components of the wetting agent may include one or more of the following ingredients: modified starch, polyvinyl alcohol (PVA), vegetable oil and non-ionic surfactant.
[0098] Before coating the sizing agent on the surface of the fiber filament, the fiber filament can be prepared by a wire drawing process.
[0099] For glass fiber, the raw material used in the drawing process can be glass. After the molten glass flows out from the tank kiln or the melting part of the crucible, it enters the main passage for clarification, homogenization and temperature adjustment, and then enters the bushing at a certain temperature, passes through the nozzle and the cooling system, and is cooled and formed to obtain fiber filaments. In the drawing process, fiber filaments of a certain diameter and a certain Tex value can be obtained by controlling parameters such as the bushing structure.
[0100] For quartz fiber, the raw material used in the drawing process can be a quartz rod with a low hydroxyl content. The diameter of the quartz rod can range from 1 to 5 mm. The quartz rod can be melted and softened by gas refining, gas continuous melting, electric melting and other processes, and then drawn into fiber filaments of a certain thickness at high speed. Similarly, after the fiber filaments are bundled, a layer of impregnating agent can be coated on the surface of the fiber bundle, and the main component of the impregnating agent can be the same as the main component of the above-mentioned slurry. The diameter of the fiber filament can be adjusted by the drawing process parameters, and the number of fiber filaments can be determined by the number of quartz rods.
[0101] S402, sizing the fiber yarn during the warping process, wherein the main component of the sizing material used is organic matter with an initial thermal decomposition temperature lower than 350° C. and being water-soluble.
[0102] In the process of making fiber cloth, the fiber yarn needs to be sized, that is, one or more layers of sizing are wrapped on the surface of the fiber yarn to protect the fiber yarn from problems such as broken yarn and hairiness during the weaving process. Similar to the sizing agent, the sizing agent does not need to be retained in the fiber cloth product. After the fiber cloth is woven, the sizing agent and sizing agent can be removed together in the subsequent desizing process.
[0103] Similar to the main component of the sizing agent, the main component of the slurry can also be an organic matter with an initial thermal decomposition temperature lower than 350°C and water-soluble, for example, it can include one or more of modified starch, PVA, vegetable oil and non-ionic surfactant. And after the main component of the slurry is treated by TGA, for example, when the temperature is increased at a rate of 10°C / min for decomposition, when the temperature is increased to 380°C, the organic matter residue is ≤50%, and after decomposition at 380°C for 2h, the organic matter residue is ≤10%, and after decomposition for 5h, the residue is ≤5%. The solubility of the slurry in an aqueous solution at 80°C can also be 100%.
[0104] The main component of the slurry and the main component of the sizing agent may be the same or different.
[0105] It should be noted that the fiber yarn can be formed by twisting fiber filaments, that is, the fiber yarn can be formed by processing the fiber filaments from the drawing process through a twisting machine to a certain twist to improve the weaving characteristics of the cloth. After twisting, the fiber yarn can be arranged in a certain number according to the different specifications of the fiber yarn, that is, the warping process is carried out. During the arrangement process, the fiber yarn is simultaneously sized, or the warp yarn is sized, that is, the sizing agent is coated on the surface of the fiber yarn to protect the fiber yarn from broken silk and hairiness problems in the subsequent weaving process, and based on the warp density requirements, multiple warp beams are combined into one to increase the warp density. This process can also be called a beam combining process.
[0106] S403, weaving the sizing fiber yarn into fiber cloth.
[0107] When weaving, the warp yarns can be inserted into the healds in sequence, for example, the odd-numbered warp yarns are inserted into the first heald frame, and the even-numbered warp yarns are inserted into the second heald frame, so as to form an opening during the weaving process. After the healds are inserted, the warp yarns are inserted into the reed in sequence. The density of the reed can determine the density of the warp yarns. The heald frame moves up and down to form an opening, and the weft yarn passes through with a high-speed jet, and the reed beats the weft to form a plain weave of warp and weft interlaced to obtain a fiber cloth. The fiber cloth obtained in this process can also be called a grey cloth.
[0108] S404, ultrasonically cleaning the fiber cloth in a temperature range of 60°C to 95°C.
[0109] During the ultrasonic immersion process, the fiber can be placed in pure water at 60℃~95℃, for example, in pure water at 70℃, 80℃, 90℃, etc., and a high-power ultrasonic generator is used to accelerate the dissolution of the slurry and sizing agent on the surface of the fiber cloth, and the slurry is removed by circulating filtration. Using pure water as a solvent for ultrasonic immersion desizing has the effects of environmental protection and low cost.
[0110] The solution used in the ultrasonic immersion process may also be any one of a methanol solution, an ethanol solution or an ether organic solution, which can increase the solubility of the wetting agent and the slurry, and further increase the removal rate of the wetting agent and the slurry.
[0111] In some embodiments, the processing time of the ultrasonic immersion process can be greater than or equal to 10 seconds. For example, during the ultrasonic immersion process, batch processing of the fiber cloth is achieved through roller transmission, and the ultrasonic immersion time of the fiber cloth can be ensured by controlling the number of rollers, the arrangement of the rollers, and the transmission line speed. Exemplarily, the ultrasonic immersion time can be greater than or equal to 20 seconds, 30 seconds, 40 seconds, 50 seconds, 60 seconds, etc.
[0112] After the ultrasonic immersion cleaning process is completed, the residual organic matter on the surface of the fiber cloth, that is, the residual slurry, can be less than or equal to 0.5%. During the ultrasonic immersion cleaning process, the residual organic matter on the surface of the fiber cloth can be reduced by adjusting process parameters such as ultrasonic immersion cleaning time, ultrasonic power, and solution concentration.
[0113] The slurry on the surface of the fiber cloth is removed by ultrasonic immersion at 60℃~95℃. The treatment temperature is low and the time is short, which can effectively reduce the energy consumption of the fiber cloth production process and improve production efficiency. In addition, desizing at a low temperature of 60℃~95℃ is less likely to cause problems such as hairiness during the processing, and the strength of the fiber cloth is less damaged. The tensile strength of the fiber cloth is higher, and it is less likely to cause problems such as hairiness during the use of the fiber cloth, avoiding continuous strong heat desizing to damage the fiber surface and affect the tensile strength of the fiber cloth.
[0114] In some embodiments, before ultrasonically immersing the fiber cloth, an oxidant aqueous solution, a weak alkali aqueous solution, or an ether organic solution may be used to swell the fiber cloth. The oxidant aqueous solution may be, for example, a hydrogen peroxide solution, a sodium bromite solution, etc., and the weak alkali aqueous solution may be, for example, a sodium 2 CO 3The aqueous solution, ether organic solution can be, for example, diethyl ether, dipropyl ether, ethyl butyl ether, etc. The temperature of the oxidant aqueous solution, weak base aqueous solution or ether organic solution can be 60° C. to 95° C., and the concentration can be 0.1% to 5%.
[0115] The fiber cloth is subjected to swelling treatment using an oxidant aqueous solution, a weak alkali aqueous solution or an ether organic solution. For the weak alkali aqueous solution, the wetting agent and the slurry on the surface of the fiber cloth can be hydrolyzed in the weak alkali aqueous solution, thereby causing the wetting agent and the slurry to swell or dissolve in the weak alkali aqueous solution. For the oxidant aqueous solution and the ether organic solution, the wetting agent and the slurry can be oxidized and swell or degrade. Therefore, the fiber cloth is subjected to swelling treatment using an oxidant aqueous solution or a weak alkali aqueous solution, which can partially remove the wetting agent and the slurry on the surface of the fiber cloth, or cause the wetting agent and the slurry to swell, thereby increasing the removal rate of the wetting agent and the slurry in the subsequent ultrasonic immersion cleaning process.
[0116] After the ultrasonic immersion process is completed, the fiber cloth can also be subjected to batch desizing, or it can also be called strong thermal desizing, that is, the fiber cloth can be subjected to high-temperature treatment in the range of 320°C to 380°C, so that the residual wetting agent and slurry on the surface of the fiber cloth are thermally decomposed to remove the wetting agent and slurry on the surface of the fiber cloth.
[0117] The treatment time of strong thermal desizing can be 20h to 40h to allow the wetting agent and slurry to be fully thermally decomposed. The treatment time of strong thermal desizing is 20h to 40h, which can refer to a duration of 20h to 40h at a high temperature in the range of 320℃ to 380℃, such as above 350℃.
[0118] The metal roller used in the strong heat desizing process can be an alloy metal with a thermal expansion coefficient less than or equal to 10ppm / ℃. The metal roller used in this process can be made of materials such as austenitic stainless steel 410, stainless invar alloy, titanium steel, etc. In the strong heat desizing process, the fiber cloth can be wound into a fiber cloth roll, and the fiber cloth roll is sleeved on the metal roller for desizing. The thermal expansion coefficient of the metal roller is less than or equal to 10ppm / ℃, which can reduce the stress on the fiber cloth caused by the thermal expansion of the metal roller. The roll length of the fiber cloth roll can be less than 2000m, and the roll length of the fiber cloth roll can refer to the length of the fiber cloth roll after it is unfolded, which is less than 2000m, so as to ensure the temperature uniformity of the inner and outer layers of the fiber cloth roll.
[0119] After strong thermal desizing treatment, the residual organic matter on the surface of the fiber cloth can be ≤0.08%.
[0120] High-temperature treatment of the fiber cloth in the range of 320°C to 380°C can reduce the damage to the surface of the fiber cloth caused by strong heat, further increase the removal rate of slurry and impregnation agent on the surface of the fiber cloth, and enhance the tensile strength of the fiber cloth.
[0121] After desizing is completed, high-pressure water can be used to pre-open the fiber cloth and remove the residual slurry adsorbed on the surface of the fiber cloth, and the fiber cloth with a clean surface can be post-processed to improve the surface properties of the fiber cloth and reduce interface loss. In the post-processing process, a coupling agent can be used to treat the surface of the fiber cloth so that the fiber cloth can be better combined with the resin during the production of the copper clad laminate. The coupling agent can be, for example, a silane coupling agent.
[0122] The number of coupling agent treatments may be at least two, and the molecular weight of the coupling agent used in each coupling agent treatment after the first coupling agent treatment is smaller than the molecular weight of the coupling agent used in the first coupling agent treatment. The molecular weight of the coupling agent used in the subsequent coupling agent treatment process is smaller than the molecular weight of the coupling agent used in the first coupling agent treatment process, which can reduce the steric hindrance effect and improve the reaction activity; and the coupling agent used in the subsequent process can synergize with the coupling agent used in the first coupling agent treatment to improve the reliability of the interface.
[0123] The coupling agent can be a silane coupling agent, which can be a long chain silane with a molecular weight of tens to hundreds or a structure such as a benzene ring and an alkyl group (such as a methoxy group or an ethoxy group). Exemplarily, the silane coupling agent can be one or more of the following: γ-aminopropyltriethoxysilane, vinyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, tris(trimethoxysilylpropyl)isocyanurate, 3-(2,3-epoxypropyloxy)propyltriethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane, dodecyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane.
[0124] The coupling agent treatment may be performed only once, so that the fiber cloth can be combined with the resin. This application does not limit this.
[0125] The fiber cloth treated with the coupling agent can be subjected to alkylation modification. In this process, a certain concentration of small molecule silane can be mixed with a suitable solvent and placed in a tank, and then the fiber cloth treated with the coupling agent is immersed in a treatment liquid at a certain line speed and temperature to perform alkylation modification on the fiber cloth. The alkylation modification process can also be performed simultaneously with the coupling agent treatment process. For example, when the coupling agent treatment is performed once, a silane coupling agent and a small molecule silane can be added simultaneously to perform surface treatment on the fiber cloth; for another example, when the coupling agent treatment is performed twice, an alkylation modification process can be performed simultaneously with the second coupling agent treatment.
[0126] The steric hindrance effect of the small molecule silane can be smaller than the steric hindrance effect of the coupling agent. For example, the molecular weight of the small molecule silane can be smaller than the molecular weight of the coupling agent, or the molecule of the small molecule silane can be smaller than the molecular weight of the coupling agent used in each coupling agent treatment in multiple coupling agent treatments, and the small molecule silane can be a silane without an active functional group at the other end of the molecular chain. Exemplarily, the small molecule silane can be methyltrimethoxysilane, methyltriethoxysilane, etc., or it can also be a chlorosilane, for example, it can be trimethylchlorosilane, triethylchlorosilane, etc. The above-mentioned small molecule silane can be dissolved in a mixed solution of methanol / water and hydrolyzed to obtain a treatment solution. The solution concentration of the small molecule silane can be 0.5% to 3%, the pH range of the solution can be 3 to 5, and the solution temperature can be 30°C to 50°C. The immersion time of the fiber cloth in the small molecule silane solution can be ≥10s, for example, ≥5min.
[0127] The fiber cloth is alkylated with small molecule silane. Since the steric hindrance effect of small molecule silane is small and its reaction activity with the hydroxyl groups on the surface of the fiber cloth is high, the remaining hydroxyl groups on the surface of the fiber cloth can be easily removed by reaction, thereby improving the loss of the fiber cloth and the loss of the copper clad laminate.
[0128] After the alkylation modification is completed, the fiber cloth can also be cured by passing through a heating furnace at 110°C to 130°C, and then removed from the surface of the fiber cloth by high-pressure water washing and deionized water soaking, and then dried to obtain the finished fiber cloth.
[0129] Figure 5 This is a comparison chart of the organic matter content remaining on the surface of a fiber cloth made by the method for making a fiber cloth provided by the embodiment of the present application and by the method for making a fiber cloth in the prior art after the fiber cloth is desized once and treated by TGA for a certain period of time. Figure 5 (a) shows the change of surface organic matter content of the fiber cloth made by the method in the prior art after one desizing and after TGA treatment. The desizing method used in the prior art is continuous strong heat desizing at a temperature of 380℃~420℃, and batch desizing at a temperature of 380℃~420℃. After one desizing, it is continuous strong heat desizing at a temperature of 380℃~420℃. The one desizing in the embodiment of the present application is ultrasonic immersion desizing.
[0130] from Figure 5It can be seen that the weight of surface organic matter in the fiber cloth obtained after a desizing in the prior art is reduced by 2.330% after 150 minutes of TGA treatment, and the weight of organic matter changes little after 100 minutes. In the embodiment of the present application, the weight of surface organic matter in the fiber cloth obtained after a desizing is reduced by 0.090% after 150 minutes of TGA treatment, and the reduction in surface organic matter is significantly less than the reduction in surface organic matter in the fiber cloth in the prior art. The organic matter ablated during the TGA treatment is the wetting agent and slurry remaining on the surface of the fiber cloth after a desizing process. The reduction in surface organic matter in the fiber cloth provided in the embodiment of the present application is less than the reduction in surface organic matter in the fiber cloth in the prior art, indicating that after the ultrasonic immersion treatment provided in the embodiment of the present application, the slurry and wetting agent on the surface of the fiber cloth are effectively removed.
[0131] The present application also provides a prepreg, which may include the fiber cloth described in the above embodiment. The method for making the prepreg may mainly include two steps: adjusting the glue and applying the glue.
[0132] The glue mixing process is to prepare the resin formula solution. During this glue mixing process, the resin, curing agent, accelerator, additive, filler, solvent, etc. can be fully mixed to form glue based on the designed board formula.
[0133] The gluing process is also the process of making prepreg. The resin content required for the prepreg can be calculated based on the basis weight, density and density of the fiber cloth and the density of the glue. In the gluing process, the glue can be transferred to the glue tank, the fiber cloth is passed through the glue tank, and a certain thickness is obtained by a metering roller, and then the solvent is removed by a continuous oven to obtain a slightly cross-linked B-stage state resin sheet. The resin sheet is also a prepreg, or it can also be called a semi-cured sheet (prepreg, PP), or a semi-cured prepreg.
[0134] The prepreg can be made by pre-impregnating with glue without filler, the pre-impregnation speed can be 5m / min, and the number of squeezing rollers can be increased to ensure the wetting effect of the fiber cloth.
[0135] Figure 6 This is a schematic diagram of the prepreg structure provided in an embodiment of the present application. The prepreg can be made by using a fiber cloth 100 with a suitable thickness and a large basis weight, and coating the surface of the fiber cloth 100 with a resin 200. The resin on the surface of the fiber cloth can be in a semi-cured state with a slight adhesiveness, which can also be called a cream layer, and the resin can also be called a resin matrix. 1 is the thickness of the fiber cloth, H 2 H is the thickness of the resin on the surface of the fiber cloth. The overall thickness of the prepreg is the sum of the thickness of the fiber cloth and the resin. 1 +2H 2 .
[0136] In some embodiments, the thickness of the cream layer may be in the range of 3 μm ≤ H 1 ≤15μm. The thickness of the cream layer ranges from 3μm to 15μm, which may mean that the thickness of the cream layer on both the upper and lower surfaces of the fiber cloth can be 3μm to 15μm. The prepreg has a smaller cream layer thickness, which can effectively reduce the resin content in the prepreg, thereby reducing the CTE of the prepreg. In addition, the fiber cloth described in the above embodiment is used to make the prepreg. The fiber cloth has the characteristics of thin thickness and large linear density, which can further reduce the resin content in the prepreg and reduce the CTE of the product.
[0137] Furthermore, the thickness of the cream layer can be 4 μm ≤ H 1 ≤6μm.
[0138] In some embodiments, the cream layer thickness may be less than the fiber cloth thickness, and the difference between the fiber cloth thickness and the prepreg thickness is 6 μm to 30 μm. Further, the difference between the fiber cloth thickness and the prepreg thickness may be controlled in the range of 8 to 12 μm, thereby obtaining a metal foil clad plate with lower CTE.
[0139] The present application also provides a metal foil clad plate, which may include the prepreg described in the above embodiment and at least two metal foils, and the prepreg may be disposed between the at least two metal foils. Exemplarily, the metal foil clad plate may be a copper clad plate, and the prepreg is disposed between at least two copper foils.
[0140] When making the metal foil-clad board, PP can be cut into a certain size and covered with metal foil of a certain thickness and size on the top and bottom. After the stacking is completed, the resin composition is solidified through a certain heating, insulation and cooling process to form a metal foil-clad board. After cooling, it is cut into a certain size to obtain a metal foil-clad board. The metal foil-clad board can be used to make a printed circuit board PCB.
[0141] Since the prepreg used in the metal foil clad plate has a lower cream layer thickness, and the fiber cloth has the characteristics of thin thickness and high linear density, the metal foil clad plate can have a better impregnation effect and is not prone to problems such as delamination and lack of glue.
[0142] Table 5 is a comparison of the copper clad laminate provided in the embodiment of the present application and the copper clad laminate in the prior art. The copper clad laminate in the embodiment of the present application can be made by using the same temperature, pressure and other conditions as those for laminating conventional glass fiber cloth, and using the above-mentioned prepreg, and covered with copper foil on the top and bottom. Among them, the XY CTE in the following table can be the planar CTE of the copper clad laminate.
[0143] Table 5
[0144] Prior art CCL1 CCL2 <![CDATA[Fiber cloth basis weight (g / m 2 )]]> 20 28.0 15.0 Fiber cloth thickness (μm) ~22 ~25 ~14 <![CDATA[Fiber cloth density (g / cm 3 )]]> 2.3 2.3 2.3 <![CDATA[Glue density (g / cm 3 )]]> 1.38 1.38 1.38 PP thickness (μm) 40 40 20 PP resin content (%) 68% 58% 56% XY CTE of pressed CCL (ppm / ℃) ~19 ~16.8 ~16.5
[0145] Among them, the above-mentioned CCL1 and CCL2 can be CCLs made of fiber cloth and prepreg provided in the embodiment of the present application. The CCL1 and CCL2 can have the same PP thickness and a relatively close fiber cloth thickness as the CCL in the prior art, wherein CCL2 can be formed by stacking two layers of PP to have the same PP thickness as CCL1 and the CCL in the prior art. By controlling the thickness of the cream layer in the prepreg, the resin content in PP can be reduced, and the planar CTE of the CCL can be reduced. In addition, by selecting the high-density fiber cloth with the above-mentioned suitable structure, basis weight and thickness to make the prepreg, the resin content can be further reduced, thereby reducing the CTE of the copper clad laminate.
[0146] In addition, as described above, the fiber cloth provided in the embodiment of the present application has the characteristics of thinness and high density by increasing the diameter of the single filament and controlling the weaving density and the number of single filaments, so that the fiber cloth has a better impregnation effect and is not prone to problems such as delamination and lack of glue caused by low resin content.
[0147] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A fiber cloth, characterized in that: Comprising multiple warp yarns and multiple weft yarns, the warp yarns and the weft yarns are respectively formed by twisting multiple filaments. The knitting density of the warp yarns is X yarns per inch, the knitting density of the weft yarns is Y yarns per inch, the number of filaments in each warp yarn is x, the number of filaments in each weft yarn is y, the diameter of each filament in each warp yarn is Dx μm, the diameter of each filament in each weft yarn is Dy μm, the thickness of the fiber cloth is t μm, and the fiber cloth satisfies any one of the following two conditions: When t ≤ 20 μm, 4 μm < Dx ≤ 6 μm, 4 μm < Dy ≤ 6 μm, X + Y ≥ 180 yarns per inch, x + y ≤ 150, or, When 20 μm < t ≤ 60 μm, 5 μm < Dx ≤ 10 μm, 5 < Dy ≤ 10 μm, X + Y ≥ 100 yarns per inch, x + y ≤ 300.
2. The fiber cloth according to claim 1, characterized in that: The basis weight of the fiber cloth is W g / m 2 The fiber cloth also meets the following conditions: when t≤20μm, 1.3 <t / (Dx+Dy)≤2,W / t≥0.85×10 6 g / m 3 .
3. The fiber cloth according to claim 1 or 2, characterized in that: The basis weight of the fiber cloth is W g / m 2 , and the fiber cloth also satisfies the following conditions: when 20μm < t ≤ 60μm, 2 < t / (Dx + Dy) ≤ 5, and W / t ≥ 0.85×10 6 g / m 3 .
4. The fiber cloth according to any one of claims 1 to 3, characterized in that When t ≤ 20 μm, 5 μm ≤ Dx = Dy ≤ 6 μm.
5. The fiber cloth according to any one of claims 1 to 4, characterized in that When 20 μm < t ≤ 60 μm, 7 μm ≤ Dx = Dy ≤ 10 μm.
6. The fiber cloth according to any one of claims 1 to 5, characterized in that X = Y.
7. The fiber cloth according to any one of claims 1 to 6, characterized in that x = y.
8. A prepreg, characterized in that: Comprising the fiber cloth according to any one of claims 1 to 7 and a resin matrix, the resin matrix is disposed on the surface of the fiber cloth, and the thickness of the resin matrix is 3 μm to 15 μm.
9. The prepreg according to claim 8, characterized in that The thickness of the resin matrix is 4 μm to 6 μm.
10. The prepreg according to claim 8 or 9, characterized in that: The difference between the thickness of the fiber cloth and the thickness of the prepreg is 6 μm to 30 μm.
11. The prepreg according to claim 10, characterized in that The difference between the thickness of the fiber cloth and the thickness of the prepreg is 8 μm to 12 μm.
12. A metal foil-clad plate, characterized in that: Comprising the prepreg according to any one of claims 8 to 11 and at least two metal foils, the prepreg is disposed between the at least two metal foils.
13. A method for producing a fiber cloth, used for producing the fiber cloth according to any one of claims 1 to 7, characterized in that: Comprising: Coating a sizing agent on the surface of the fiber filaments, the main component of the sizing agent is an organic compound with an initial thermal decomposition temperature lower than 350 °C and having water solubility; Sizing the fiber yarns during the warping process, the main component of the sizing slurry used in the sizing process is an organic compound with an initial thermal decomposition temperature lower than 350 °C and having water solubility, and the fiber yarns are formed by twisting multiple fiber filaments; Weaving the sized fiber yarns into a fiber cloth; Performing ultrasonic immersion cleaning on the fiber cloth within a temperature range of 60 °C to 95 °C.
14. The manufacturing method according to claim 13, characterized in that: The solution used for the ultrasonic immersion cleaning is any one of the following solutions: Pure water, methanol solution, ethanol solution, ether organic compound solution.
15. The production method according to claim 13 or 14, characterized in that: The main components of the sizing slurry and the sizing agent include one or more of the following: Modified starch, polyethylene glycol, vegetable oil, non-ionic surfactant.
16. The method according to any one of claims 13 to 15, characterized in that: Before performing ultrasonic immersion cleaning on the fiber cloth, the method further includes: Swelling the fiber cloth using any one of an oxidant aqueous solution, a weak base aqueous solution, and an ether organic compound solution.
17. The manufacturing method according to claim 16, characterized in that: The temperature of the solution used for the swelling treatment is 60 °C to 95 °C, and the concentration is 0.1% to 5%.
18. The method according to any one of claims 13 to 17, characterized in that: The treatment time of the ultrasonic immersion cleaning is greater than or equal to 10 s.
19. The method according to any one of claims 13 to 18, characterized in that: After performing ultrasonic immersion cleaning on the fiber cloth, the method further includes: Performing strong heat desizing treatment on the fiber cloth obtained by ultrasonic immersion cleaning, the temperature of the strong heat desizing treatment is 320 °C to 380 °C, and the time is 20 h to 40 h.
20. The manufacturing method according to claim 19, characterized in that: The metal roller used in the strong thermal desizing treatment is an alloy metal with a thermal expansion coefficient less than or equal to 10 ppm / °C.
21. The method according to claim 19 or 20, characterized in that: After the fiber cloth obtained by ultrasonic immersion is subjected to a strong thermal desizing treatment, the method further comprises: The fiber cloth is treated with a coupling agent, and the fiber cloth treated with the coupling agent is alkylated and modified by using small molecule silane.
22. The manufacturing method according to claim 21, characterized in that: The coupling agent treatment is performed at least twice, and the steric hindrance effect of the coupling agent used in each coupling agent treatment after the first coupling agent treatment is smaller than the steric hindrance effect of the coupling agent used in the first coupling agent treatment.
23. The method according to claim 21 or 22, characterized in that: The small molecule silane is any one of the following silanes: Methyltrimethoxysilane, methyltriethoxysilane, trimethylchlorosilane, triethylchlorosilane.